Alignment in second language speakers' perceptions of interaction and its relationship to perceived communicative success. (August 2022) - Tekin, Oguzhan; Trofimovich, Pavel; Chen, Tzu-Hua; McDonough, Kim
Abstract: Conversation is a co-constructed social activity, and interlocutors, including second language (L2) speakers, frequently align in their linguistic and nonlinguistic behaviors to create shared understanding. Given that L2 speakers make assumptions about their interlocutors, this exploratory study examines whether their perceptions about linguistic, socio-affective, and behavioral dimensions of interaction align. It also explores whether such alignment is related to their agreement about the success of the conversation. Eighty-four pairs of L2 English university students completed a 10-min academic discussion task, subsequently rating each other's comprehensibility, fluency, anxiety, motivation, and collaboration. At the end of a 30-min session, they also assessed the communicative success of their conversational experience. Speakers were generally aligned in their evaluations of each other and in their perception of communicative success, with alignment operationalized as the difference between the partners' scores. Although alignment in all dimensions of interaction was associated with perceived communicative success, collaboration had the strongest relationship (0.40 or 16% shared variance). The findings provide preliminary evidence that L2 speakers' alignment in perceived dimensions of interaction, particularly collaboration, is associated with their perceived communicative success. Highlights: L2 speakers' interactive alignment in perceived linguistic, socio-affective, and behavioral dimensions was linked to communicative success. Alignment in perceived collaboration had the strongest link to perceived communicative success. Perceived collaboration encompassed various dimensions of speakers' interactive experience.